Pediatric Cataract - Bharat Patil; Reetika Sharma; Bhagbat Nayak; Gautam Sinha; Sudarshan Khokhar (Delhi Journal of Ophthalmology)
Paediatric cataract is one of the most important surgically treatable causes of childhood blindness. Treating pediatirc cataract has a large impact on society as ‘lost blind years’ can be saved. Various morphological types are known of which zonular has the best visual prognosis. Rubella accounts for the most common preventive cause for pediatrc cataract. Intraoperative biometry plays an important role though in coperative children optical biometry may be suitable option. Since the pediatric eye and pediatric lens is not a minature adult eye and lens repsectively, surgical steps needs to be modified. Intraocular lenses (IOL) provide the best available option for visual rehabilitation after removal of cataract because of the constant visual input provided. Poor intraocular lens power predictability, increased inflammation, postoperative complications and the technical difficulty of surgery are the main concerns for IOL implantation. Surgery is just a step towards management of pediatric cataract, amblyopia therapy, glasses correction, and log term follwup are essetinal for better outcomes.